A novel method of high‐purity extracellular vesicle enrichment from microliter‐scale human serum for proteomic analysis. Issue 3 (1st February 2021) - Ji, Xiaohui; Huang, Sisi; Zhang, Jie; Bruce, Terri F.; Tan, Zhijing; Wang, Donglin; Zhu, Jianhui; Marcus, R. Kenneth; Lubman, David M.
Abstract: We have developed a rapid, low‐cost, and simple separation strategy to separate extracellular vesicles (EVs) from a small amount of serum (i.e., <100 μL) with minimal contamination by serum proteins and lipoprotein particles to meet the high purity requirement for EV proteome analysis. EVs were separated by a novel polyester capillary channel polymer (PET C‐CP) fiber phase/hydrophobic interaction chromatography (HIC) method which is rapid and can process small size samples. The collected EV fractions were subjected to a post‐column cleanup protocol using a centrifugal filter to perform buffer exchange and eliminate potential coeluting non‐EV proteins while minimizing EV sample loss. Downstream characterization demonstrated that our current strategy can separate EVs with the anticipated exosome‐like particle size distribution and high yield (∼1 × 10 11 EV particles per mL of serum) in approximately 15 min. Proteome profiling of the EVs reveals that a group of genuine EV components were identified that have significantly less high‐abundance blood proteins and lipoprotein particle contamination in comparison to traditional separation methods. The use of this methodology appears to address the major challenges facing EV separation for proteomics analysis. In addition, the EV post‐column cleanup protocol proposed in the current work has the potential to be combined with other separation methods, such as ultracentrifugation (UC), to further purify the separated EV samples. Abstract :